2015
DOI: 10.7150/jca.11997
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Artifacts, Including Spurious Chimeric RNAs with a Short Homologous Sequence, Caused by Consecutive Reverse Transcriptions and Endogenous Random Primers

Abstract: Recent RNA-sequencing technology and associated bioinformatics have led to identification of tens of thousands of putative human chimeric RNAs, i.e. RNAs containing sequences from two different genes, most of which are derived from neighboring genes on the same chromosome. In this essay, we redefine “two neighboring genes” as those producing individual transcripts, and point out two known mechanisms for chimeric RNA formation, i.e. transcription from a fusion gene or trans-splicing of two RNAs. By our definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 163 publications
0
72
0
Order By: Relevance
“…Development of novel computational methodology has relaxed many of these assumptions, including algorithms that discover de novo splice sites, but even now it remains a significant challenge to distinguish apparently novel splicing or expression events from biochemical noise [30]. Therefore, most algorithms originally designed to detect novel splicing (including ab initio attempts to annotate the transcriptome [31] and even algorithms intended to detect gene fusions in cancer) must impose ad hoc filters due to high false positive rates [32]. …”
Section: Original Algorithms To Detect Circrna Expressionmentioning
confidence: 99%
“…Development of novel computational methodology has relaxed many of these assumptions, including algorithms that discover de novo splice sites, but even now it remains a significant challenge to distinguish apparently novel splicing or expression events from biochemical noise [30]. Therefore, most algorithms originally designed to detect novel splicing (including ab initio attempts to annotate the transcriptome [31] and even algorithms intended to detect gene fusions in cancer) must impose ad hoc filters due to high false positive rates [32]. …”
Section: Original Algorithms To Detect Circrna Expressionmentioning
confidence: 99%
“…A number of computational and statistical considerations must also be taken into account during circRNA detection and quantification (Szabo et al, 2015). As such, and given the homology between and within genes in almost all genomes, which can lead to read misalignments (Szabo et al, 2015), the highly precise and sensitive detection of RNA splicing into linear or circular molecules remains a significant challenge in the field (Engström et al, 2013;Peng et al, 2015). A user-friendly, searchable database of identified circRNAs is curated by the Rajewsky lab and can be found at circbase.org (Glažar et al, 2014).…”
Section: Bioinformatic and Statistical Identification Of Circular Rnasmentioning
confidence: 99%
“…Initially believed to be isolated to blood-based neoplasia (Daley and Ben-Neriah, 1991) and later shown to be common in solid tumors (Barr, 1998;Aman, 1999), fusion transcripts received significant attention due to their diagnostic, prognostic and sometimes remarkable therapeutic implications (Burchill, 2003;Schnittger et al, 2003;An et al, 2010). Discussion of fusion transcripts detected in normal tissues centered on apparently benign events resulting from co-transcription of neighboring genes or more controversially from trans-splicing (Akiva et al, 2006;Peng et al, 2015;Babiceanu et al, 2016;Yuan et al, 2017;He et al, 2018). Reports of fusions in the context of inherited disease existed only in isolated case studies and were not systematically reported on until 2019 (Oliver et al, 2019b).…”
Section: Adapting Fusion Detection To Rare Diseasementioning
confidence: 99%